THE URGENCY OF IMPROVING THE COMPETENCY OF THE TREASURER OF FAKFAK REGIONAL APPARATUS ORGANIZATIONS ON FINANCIAL REPORTING PERFORMANCE - Andi Tamher; Sri Rahayu; Vidia Gati; Christina Wulansari (Sean Institute, 2023)
Reporting on budget use is crucial and determines the accuracy of financial circulation within the Fakfak Regency Government. Therefore, increasing the competency factor for preparers of financial reports has an important role in achieving timely reporting performance, and the substance of the report meets aspects of transparency and accountability as stipulated in applicable regulations. The research aims to find forms of increasing competency factors for treasurers who are tasked with preparing financial reports in various Regional Government Organizations in Fakfak Regency. The research was carried out during July – December 2023. The research method was descriptive with a combination approach of quantitative and qualitative analysis. Data was obtained through a direct survey of respondents who had been determined deliberately. The data obtained is given a weight value based on assessment indicators obtained from the results of preliminary research. Test the validity and reliability of the data in a gradual and structured manner using a triangulation and role sharing approach. The research results are presented in the form of a spider web diagram which is equipped with illustrations of shift share gap values, Spearman correlation analysis , regression equation models obtained from the SPSS version 2.3 statistical tool. as well as implementation strategies using the SWOT-BSC approach.